2019
DOI: 10.1093/rpd/ncz188
|View full text |Cite
|
Sign up to set email alerts
|

A WALK-IN TYPE CALIBRATION CHAMBER FACILITY FOR 222Rn MEASURING DEVICES AND INTER-COMPARISON EXERCISES

Abstract: A walk-in type 222Rn calibration chamber of volume 22.7 m3, which has traceability to international standards, is established at the Centre for Advanced Research in Environmental Radioactivity, Mangalore University, India. It has a human–machine interface communication system, a programmable logic controller and sensor feedback circuit for controlling and data acquisition of relative humidity (RH) and temperature (T). An innovative method for the generation of desired 222Rn concentration (a few hundred Bq m−3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The details of soil gas 222 Rn extraction were described in our earlier publications ( Karunakara et al, 2015 , 2020 ; Sudeep et al, 2012 ; Shetty et al, 2020 ). A soil gas probe (STITZ, Genitron Instruments, Germany) was inserted inside the ground to a depth of 0.8–1 m since the 222 Rn concentration in soil gas increases exponentially with depth and saturates to an equilibrium concentration at a depth greater than about 0.8–1 m ( Nazaroff and Nero, 1988 ; Al-Azmi and Karunakara., 2007 ; Al-Azmi, 2009 ; Sudeep et al, 2012 ; Katalin et al, 2013 ; Shetty et al, 2019 ; 2020 ; Karunakara et al, 2015 , 2020 ). A pump with adjustable flow rates (10–80 L min −1 , depending upon the experimental requirements) was connected to the probe to draw the soil gas and inject it into the workplace as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of soil gas 222 Rn extraction were described in our earlier publications ( Karunakara et al, 2015 , 2020 ; Sudeep et al, 2012 ; Shetty et al, 2020 ). A soil gas probe (STITZ, Genitron Instruments, Germany) was inserted inside the ground to a depth of 0.8–1 m since the 222 Rn concentration in soil gas increases exponentially with depth and saturates to an equilibrium concentration at a depth greater than about 0.8–1 m ( Nazaroff and Nero, 1988 ; Al-Azmi and Karunakara., 2007 ; Al-Azmi, 2009 ; Sudeep et al, 2012 ; Katalin et al, 2013 ; Shetty et al, 2019 ; 2020 ; Karunakara et al, 2015 , 2020 ). A pump with adjustable flow rates (10–80 L min −1 , depending upon the experimental requirements) was connected to the probe to draw the soil gas and inject it into the workplace as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The 222 Rn detection range of the scintillation cell-based monitor was 8 Bq m −3 to 50 MBq m −3 , while the ionization chamber-based monitor was 2 Bq m −3 to 20 MBq m −3 . The detailed specification of these instruments was published previously ( Al-Azmi and Karunakara, 2007 ; Karunakara and Al-Azmi, 2010 ; Karunakara et al, 2015 ; Sudeep et al, 2017 ; Sahoo et al, 2017 ; Shetty et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…To proceed further, we make an important assumption that the injected activity spreads rapidly in the chamber due to a mixing element such as fan, leading to spatially uniform 222 Rn concentration. Detailed studies conducted with a 22.7 m 3 calibration chamber at CARER 8,13 with a mixing fan of capacity 3,620 m 3 h −1 have shown that time required for attaining uniform concentration is < 10 min, which is much smaller than the pump OFF period (T 2 ). With this experimental data we can convert the activities A n 's to concentrations C n ' as follows:…”
Section: Mathematical Formulation Of the Model And Solutionsmentioning
confidence: 99%
“…Testing and calibration of 222 Rn detectors in large volume walk-in type calibration chambers are carried out, mainly by three operational modes: (1) dynamic mode-in which 222 Rn rich air from the source is continuously pumped to the chamber through the inlet and simultaneously maintaining the outlet in the open condition to attain the concentration levels [3][4][5] , (2) static mode-in which 222 Rn laden air is filled once to achieve desired initial concentration value and the experiment is performed during the decay of 222 Rn [5][6][7] , and (3) semi-dynamic mode-in which, initially 222 Rn is injected into the chamber to obtain the desired value and then switched over to a pulsed mode of injection so that concentration is maintained within a certain band of the desired value. The periodicity of 222 Rn injection is adjusted in such a way that the loss of 222 Rn due to leak and decay is just compensated 8,9 . Calibration exercise at a low level (~ 1,000-5,000 Bq m −3 ) 10-12 demand a steady 222 Rn concentration for considerably long-time durations, from a few weeks to a few months.…”
mentioning
confidence: 99%
See 1 more Smart Citation